Use of Styrofoam Concrete in Construction Industry – A Review - MOHAMAD NASRI, MUHAMMAD HAFIZ BIN; Nurazuwa Md Noor (Recent Trends in Civil Engineering and Built Environment, 2022)
Styrofoam concrete is one of the concrete innovation applied to the building. The focal points of Styrofoam concrete are light and quick material on building work. The Styrofoam was utilized to increments the compressive quality and flexural quality of the concrete. Styrofoam concrete was lightweight and has lower thickness compared to ordinary concrete, that’s the reason why lightweight concrete has been applied to framework buildings. Styrofoam was known as a critical portion of this issue, since its non-biodegradable material leads to more prominent contamination, its reusable in numerous forms but it difficult to crush. The main points for this literature review about styrofoam concrete was on mechanical and durability performance. Scopus was the website to search the database for this study. The systematic literature review may likewise incorporate a quantitative pooling of information, called a Meta-analysis. From this systematic literature review on styrofoam concrete, it can prove that styrofoam concrete can be used in civil engineering works on the lightweight concrete. Styrofoam can be good substitute to the aggregates in the lightweight concrete but its need the correct percentage of styrofoam used.